AKRONIM MAJEMUK DALAM TEKS ARAB MODERN - gazali, erfan (EL-IBTIKAR, 2013)
Thisstudyaddressthe phenomenon ofthe Arabicthe so-called multiple acronyms as commonly used inthe academicliteratureandmediainformatics. The issue raised here is concernedÂ  with the use of acronym within acronym such as Ø§ÙÙÙØ±Ø·ÙØ³Ù (electromagnetic), thiswordisderived from Ø§ÙÙÙØ±Ø¨Ø§Ø¡ andÙÙØºÙÙØ§Ø·ÙØ³ÙÙÙ, word ofØ§ÙÙÙØ±Ø¨Ø§Ø¡(electricity)is taken from thePersianwordoriginally is acombination ofÚ©Ø§Ù (straw) and Ø±ÙØ¨ÙØ§Û (attractive).Theory ofacronyms(Faris: 271), (Ahmad, 1980:60), (Nihad,1984:67), are the foundation forthe discussionof thisreview. Arabsocietieshave knownof thisphenomenonfor a long time,abbreviatetechniquesknown in ArabicwithAnNaht.Thiswas shown bythe presence ofthe wordsacronyms(abbreviations) asAbdariword(Abd al-Dar) andAbshami(Abd al-Sams) asthe names of thetribes, the appearance of wordsinbriefin the presentincreasing fromthe previousperiod, especiallythe needsof thescientificterminologyin translatingforeign languagesintoArabicequivalents. As the sayingÙØÙØ§Ø¦ÙØ§Øªdrawnfrom thetwowordsareabreviatedÙØÙ and ÙØ§Ø¡ asa synonym forcarbohydrates. But phenomenons of multiple acronyms arenothing newandthere has been nodiscussionaboutthisin the literature ofArabiclanguage.Â Kata kunci : multiple acronyms, scintific terminology. AnNaht